Patterns of emotional-cognitive functioning in pediatric conversion patients: implications for the conceptualization of conversion disorders - Kozlowska, Kasia; Scher, Stephen; Williams, Leanne M (Psychosomatic medicine, 2011)
To examine patterns of emotion processing in children and adolescents with conversion disorders and to determine whether those patterns are associated with particular clusters of conversion symptoms. Autobiographical narratives were used to investigate the organization of information about distressing feelings and memories. Structured interviews about attachment relationships and autobiographical events were administered to 76 controls and 76 matched subjects aged 6 to 18 years. Age-appropriate assessments of attachment were used: the School-aged Assessment of Attachment for children and the Transition to Adulthood Attachment Interview for adolescents. Patterns of emotion processing were identified using dynamic-maturational model discourse analysis and categorized into four clusters: inhibitory, normative/balanced, coercive-preoccupied, and mixed inhibitory and coercive-preoccupied. These clusters were then cross-tabulated with the sensorimotor characteristics of children with conversion disorders. Emotion processing in children with conversion disorders was categorized as psychological inhibition (57%), psychological coercion-preoccupation (34%), and mixed (9%). Psychological inhibition was associated with negative conversion symptoms (discrete sensorimotor deficits, p = .003) and positive conversion symptoms (tremors and tics, p = .04). Psychological coercion-preoccupation was associated with all other disturbances of motor function: bizarre gaits and postures, whole-body floppiness, and refusals to move (p < .0001). Nonepileptic seizures occurred across both groups (56% versus 42%, p = .8). Contrary to the classic understanding of conversion disorder as a unified diagnostic entity with diverse symptoms, this study identified two distinct subtypes of conversion patients-those using psychological inhibition and those using psychological coercion-preoccupation-whose symptoms fell into discrete clusters. Further research is needed to determine the neural mechanisms underlying these processes.